1999
DOI: 10.1046/j.1365-3180.1999.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea resistance in Lindernia micrantha, an annual paddy weed in Japan

Abstract: Resistance to sulfonylurea herbicides, including bensulfuron-methyl, pyrazosulfuron-ethyl, imazosulfuron and ethoxysulfuron, was discovered in naturally occurring populations of Lindernia micrantha D. Don in rice ®elds that had been treated with sulfonylurea-based herbicides for 3±7 consecutive years. The resistant biotype was approximately 80»300 times more resistant than the susceptible one to the above four sulfonylurea herbicides. This is the second con®rmed occurrence of herbicide resistance resulting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 7 publications
1
20
0
2
Order By: Relevance
“…3. The trend obtained is consistent with recent reports on whole‐plant responses to SU herbicides in Japan (Wang et al 1997; Itoh et al 1998; Itoh et al 1999). Increasing the herbicide rate results in a decrease in shoot and root length.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3. The trend obtained is consistent with recent reports on whole‐plant responses to SU herbicides in Japan (Wang et al 1997; Itoh et al 1998; Itoh et al 1999). Increasing the herbicide rate results in a decrease in shoot and root length.…”
Section: Resultssupporting
confidence: 92%
“…Parallel dose‐response curves (i.e. with a common slope) between the resistant and susceptible biotypes were assumed in curve‐fitting, which was also was done in previous studies (Itoh et al 1999; Lee & Owen 2000;Wang et al 2000). The log‐logistic model was fitted to the data by using SAS release 6.12 (SAS Institute Inc., Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, index of resistance (IR) of 65 was determined based on biomass reduction, for Amaranthus quitensis H.B.K. Studying sulfonylurea effects to Lindernia micrantha D., Itoh et al (1999) have found that although this group of herbicides causes decrease in these parameters in both biotypes (R and S), the R biotype produced more dry weight than the S one under all rates of herbicide applied, which makes dry weight a reliable parameter for monitoring sulfonylurea-resistance of the said species. Furthermore, based on dry weight reduction, an IR of 170 was reported in imazethapyr-resistant wild population of H. annuus (Al-Khatib et al, 1998) which is similar to the level of tolerance to imazethapyr found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary investigations have revealed that a pre-emergence application of pendimethalin suppresses weed growth, when supplemented with a postemergence application of bispyribac (Mahajan and Timsina 2010). Simultaneously, different biotypes showing resistance to prevalent herbicides are known to have emerged in the United States (Fischer et al 2000), Malaysia (Watanbe, Ismail, and Ho 1997), Japan (Itoh, Wang, and Ohba 1999), and Korea (Park, Kim, and Oh 1997). In the United States, multiple resistances to several chemical classes of herbicides have occurred in a single weed species commonly found in rice fields in California (Fischer et al 2000).…”
mentioning
confidence: 99%